A linear Programming Model to Investigate the Economies of Remanufacturing under Limited Component Durability - Saki Tavandashti, Samira (2011)
Throughout this decade, closed loop supply chain (CLSC) has received a growing attention due to the increase of product returns. Firms now are aware of the economic advantages of value recovery of returns through remanufacturing. Besides the potential benefits of reuse activities, governmental legislation, environmentally conscious and customer expectations forced the enterprises to undertake the responsibility of their products from cradle to grave. In this study an integration of analytical process and linear programming approach is proposed to quantify the potential cost-savings can be achieved in a production system where returns are collected, remanufactured and finally remarketed as perfect substitutes of new products. When the system component and limitations are carefully defined, this approach proved to be a strong tool applicable for any industry. Special attention is paid to modelling the fundamental constraint of CLSC termed limited component durability. Sensitivity analysis of developed model has been done to reflect the impact of variation in tangible and intangible factors on manufacturer’s value recovery function. The results demonstrate the necessity of precious coordination of the cost structure, collection rate, remanufacturing yield, Lead time and component durability in term of maximum number of life to minimise the total production cost in the system. Key words: closed loop supply chain; value recovery; remanufacturing; linear programming limited component durability; sensitivity analysis